Historical incidence of mid‐autumn wind storms in New England. (4th October 2020) - Simonson, Julia M.; Birkel, Sean D.; Maasch, Kirk A.; Mayewski, Paul A.; Lyon, Bradfield; Carleton, Andrew M.
Abstract: New England has seen a number of mid‐autumn (October–November) wind storms—high‐wind events associated with extratropical cyclones—in recent years that have produced extensive infrastructure damage, raising concerns that these events may become more common in a changing climate. Storms developing at this time of year are unique in that they can have dominant cold‐season characteristics while also being fueled by warm‐season moisture sources (such as the remnants of tropical cyclones) or the result of an extratropical transition. To provide insights on the behavior of such storms, we explore recent storm frequency and intensity by using reanalysis and station‐based meteorological observations onward from 1979. Variables taken into consideration include 10 m wind speed, sea‐level pressure and precipitation. The results do not show a statistically significant increase in the overall frequency of mid‐autumn wind storms nor of their intensity with respect to central pressure or surface wind speeds. However, there is a statistically significant trend toward increasing precipitation accompanying wind storms with maximum 10 m wind gusts greater than 26 m⋅s −1 (58 mph). While stronger high‐wind events tend to be associated with lower central sea‐level pressure values and substantial intensification rates, other factors such as storm tracks and the pressure gradient across the New England region also affect the development and overall impact of storms. This study highlights the variety of elements, such as the background climate conditions, which could potentially increase the risk of wind damage in a warming world. Abstract : New England has seen a number of mid‐autumn wind storms in recent years that have produced extensive infrastructure damage, raising concerns that they may become more common in a changing climate. To provide insights on their behavior, this study explores recent storm frequency and intensity using reanalysis and station observations. Although the results do not show statistically significant shifts in wind storm frequency or intensity, there are a variety of elements which could potentially increase the risk of wind damage.